Phylogeography of the Siberian roe deer in Eurasia and origin of the Siberian MtDNA lineage in European roe deer populations - Plis, Kamila; Niedziałkowska, Magdalena; Danilkin, Aleksey; Kholodova, Marina; Zvychaynaya, Elena; Kashinina, Nadezhda; Bunevich, Aleksey; Okhlopkov, Innokentiy; Mamaev, Nikolay; Kusza, Szilvia; Paule, Ladislav; Veeroja, Rauno; et al. (Springer Nature, 2025)
The Siberian roe deer (Capreolus pygargus) is distributed throughout continental Asia. In Eastern Europe, individuals of the European roe deer species (Capreolus capreolus) displaying mitochondrial DNA (mtDNA) of C. pygargus have been recorded. However, it is not clear if the origin of this introgression is an effect of natural processes or a consequence of human-mediated translocation of the Siberian roe deer. Only a large-scale phylogeographic analysis, spanning both the natural range of C. pygargus and the introgression zone, can answer this question. To reveal the cause of the introgression and to provide the most comprehensive picture of Siberian roe deer phylogeography, we analysed the mtDNA control region fragment (610 bp) of 352 individuals combined with 132 sequences available in GenBank, covering a vast region extending from Eastern Europe to Eastern Asia. We detected 101 mtDNA haplotypes and 6 haplogroups. The proportion of different haplogroups, varying along longitudinal gradients, showed a notable shift in the central parts of Siberia. Haplogroups B and D were the most frequent in the introgression zone. Seven genetic clusters of Siberian roe deer, including two in the introgression zone, were detected. MtDNA diversity of Siberian roe deer proved to be greater than previously documented. Two genetically and evolutionarily distinct haplogroups, occurring predominantly in Europe, appear to be remnants of natural interbreeding between the two roe deer species that could have occurred during one hundred thousand years ago in at least two different time periods. Additionally, past human-mediated translocations of the Siberian roe deer contributed to the observed introgression.
Keywords: Capreolus pygargus; Mitochondrial DNA; Genetic diversity; Siberian lineage; Introgression; Translocations